Towards keeping diesel fuel supply and demand in balance: dual-fuelling of diesel engines with natural gas - Hegab, Abdelrahman; La Rocca, Antonino; Shayler, Paul J. (Elsevier, 2016)
With the continuous growth of energy demand for the commercial transport sector, the market share of diesel vehicles is rising in several areas worldwide. Global demand for transport energy is therefore believed to be strongly skewed towards heavier fuels; particularly diesel. The strengthen emissions legislation is another issue facing the current generation of diesel engines; where there is an increasing concern with their high NOx and PM emissions. Dual-fuelling of diesel engines with natural gas (NG) stands as an attractive solution to reduce the dependence on diesel fuel and mitigate the harmful effects of diesel engines emissions. The main attractions of NG as a contributor to a more sustainable fuel market include its lower carbon content and relatively higher natural reserves, in addition to the renewable aspect of methane production from biogas.